ANALISIS PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011 - Pratama Agustin Indah Sari (Jurnal Manajerial, 2018)
This research had a purpose to provide empirical evident about factors that financial distress of property and real estate company ware listed in Bursa Efek Indonesia 2011. The examined factors on this research ware profit margin, profitability, financial leverage, liquidity, position of cash, Growth, and efisiently of operation. The samples consist of 34 company which had not on financial distress condition, and 6 company which had financial distress. The statistic method used to test on the research hypothesis is logit regression. The result showed that profit margin, profitability, financial leverage, liquidity, position of cash, Growth, and efisiently of operation had classification power to know financial ratio’s influence financial distress property and real estate company ware listed in Bursa Efek Indonesia 2011. This research also indicated that profit margin, profitability, financial leverage, liquidity, position of cash, Growth, and efisiently of operation ratios ware statistically different for financial distress company and non financial distress company, finally only profitability was significant variables in determinant financial distress company.